Novel Aloe Vera fiber reinforced biodegradable composites—Development and characterization. (October 2016) - Chaitanya, Saurabh; Singh, Inderdeep
In the current research enterprise, behavior of novel bio-composites incorporating Aloe Vera fibers in biopolymer matrix (polylactic acid) has been experimentally examined in comparison to Sisal fiber reinforced bio-composites. These bio-composites were melt blended using single screw extruder prior to injection molding. The effect of fiber weight fraction (10–20–30%) and fiber surface modification on mechanical behavior of developed bio-composites was investigated. Alkaline treatment using sodium hydroxide concentration of 5% was used for fiber surface modification. Both alkali treated and raw fibers were characterized using Fourier transform infrared spectroscopy, thermogravimetric analysis and scanning electron microscope. Thermal stability of the fibers improved after alkaline treatment. The mechanical characteristics of developed bio-composites exhibited an improvement with increasing fiber concentration. Alkaline treatment of fibers further improved the tensile, flexural and compressive properties of developed bio-composites, while their impact properties declined compared to raw fiber reinforced bio-composites. Moreover, from the results, it is evident that the characteristics of Aloe Vera fiber reinforced bio-composites are comparable to Sisal fiber reinforced bio-composites and the developed bio-composites have the potential to be used in various automotive, furniture and architectural applications.